HYDROCHEMICAL MODELING OF COUPLED C AND N CYCLING IN HIGH-ELEVATION CATCHMENTS: IMPORTANCE OF SNOW COVER - Meixner T.; Bales R.C. (My University, 2003)
Several ecosystems in the western US are already undergoing nitrogen (N) saturation, a condition where previously N limited ecosystems are no longer N limited. This state of N saturation leads to adverse impacts on terrestrial ecology and water quality. Due to the complexities of terrestrial carbon-nitrogen cycling, integrated hydrologic-biogeochemical modeling provides a tool to improve our understanding and discern between the impacts of changes in N deposition from changes in other ecosystem processes. A model of biogeochemical processing in alpine watersheds was developed and applied to the Emerald Lake watershed. Simulations of major terrestrial carbon and nitrogen pools and fluxes were adequate. The use of snow cover information to estimate soil temperatures improved model simulations indicating that snow cover processes need to be incorporated into biogeochemical models of seasonally snow covered areas. The model simulated mineral nitrogen processes well but significant changes in denitrification and dissolved organic nitrogen export processes appear to be necessary. Our results also showed that variations in snow cover duration have more of an impact on mineral N export, plant uptake and mineralization than appears possible due to changes in atmospheric deposition.